A User’s Guide to the Magnetically Connected Space Weather System: A Brief Review - Beedle, Jason M. H.; Rura, Christopher E.; Simpson, David G.; Cohen, Hale I.; Moraes Filho, Valmir P.; Uritsky, Vadim M. (Frontiers in Astronomy and Space Sciences, 2022)
This article provides a concise review of the main physical structures and processes involved in space weather's interconnected systems, emphasizing the critical roles played by magnetic topology and connectivity. The review covers solar drivers of space weather activity, the heliospheric environment, and the magnetospheric response, and is intended to address a growing cross-disciplinary audience interested in applied aspects of modern space weather research and forecasting. The review paper includes fundamental facts about the structure of space weather subsystems and special attention is paid to extreme space weather events associated with major solar flares, large coronal mass ejections, solar energetic particle events, and intense geomagnetic perturbations and their ionospheric footprints. This paper aims to be a first step towards understanding the magnetically connected space weather system for individuals new to the field of space weather who are interested in the basics of the space weather system and how it affects our daily lives.